Global consumer culture: consequences for consumer research. Issue 4 (8th July 2019) - Torelli, Carlos J.; Stoner, Jennifer L.
Abstract : Purpose: The purpose of this paper is to comment on the conceptual framework highlighting the reinforcing nature of global consumer culture. Design/methodology/approach: The approach is conceptual with illustrative examples. Findings: The authors integrate the conceptual framework that highlights the reinforcing nature of global consumer culture with recent findings about the psychology of globalization. Specifically, the authors bring attention to the perceptual, cognitive and motivational consequences of globalization, as well as its effects on consumer identification. The authors illustrate how this integration provides insights for better predicting consumer behavior in a globalized world. Research limitations/implications: One key aspect of globalization is the creation of multicultural spaces in contemporary societies. Taking a psychological approach, the authors discuss how consumers respond to the process of culture mixing at the heart of globalization. This has consequences for marketers' global endeavors and provides a nuanced understanding of consumer behavior in a globalized world. Originality/value: The paper integrates a novel framework with recent findings about the psychology of globalization, opening avenues for future research on global consumer cultures.